IMPLEMENTING INTEGRATIVE TEACHING IN FOREIGN LANGUAGE LESSONS THROUGH THE STEAM APPROACH - Xudoyarova Dildora Najmidinovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the implementation of integrative teaching in foreign language lessons through the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach. The study analyzes how combining linguistic, scientific, technological, artistic, and mathematical content within an interdisciplinary framework enhances students’ critical thinking, creativity, and communicative competence. By applying STEAM-based integrative strategies, students engage in project-based learning, problem-solving tasks, and collaborative activities that mirror real-world contexts. The findings indicate that this approach promotes motivation, interdisciplinary understanding, and the development of both cognitive and communicative skills, preparing learners for effective participation in global academic and professional environments.